Evaluasi Dan Perancangan Antarmuka Pengguna Aplikasi On Demand Berbasis Mobile Dengan Menerapkan Human-Centred Design (Studi Kasus: Mangjek Indonesia) - Ardeni Bayu Praditya; Admaja Dwi Herlambang; Mochamad Chandra Saputra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The rise of On Demand application makes business people compete in creating applications based on customer demands. There are a lot of On Demand applications in Indonesia, it makes users are more selective in selecting On Demand applications. Mangjek is one of the On Demand applications which is operated in Palembang. The pre-research result shows application users complaints about Driver Mangjek application interface. Those complaints show that the interface is less understandable and complicate in usage. Therefore, in this research, there will be interface design for Driver Mangjek application interface which is easily understandable by the users. The method used in this interface design is Human-Centred Design by considering android design principles and Adaptive User Interface design rules. Users satisfaction to the interface will be evaluated by using instrument which is the adaptation result of Questionnaire for User Interaction Satisfaction involving 90 respondents. The research result shows that there are users satisfaction enhancements to the interface after applying application interface improvement. The enhancements are in 5 aspects, those are: (1) Application Interface, it's increasing from 3.26 to 6.36; (2) Language usage, it's increased from 3.75 to 5.67; (3) Learning, it's increasing from 3.89 to 5.36; (4) Online Helps, it's increasing from 1.95 to 4.71; (5) Online Tutorial, it's increasing from 1.60 to 6.34.